Hubungan Penguasaan Kosakata Terhadap Keterampilan Siswa Kelas IV SD Negeri 28 Singkawang - Gitari, Vindy Ariesta; Basith, Abd.; Yanti, Lili (Jurnal Gentala Pendidikan Dasar, 2025)
This study aims to determine: (1) the vocabulary mastery of fourth-grade students at SDN 28 Singkawang, (2) their speaking skills, and (3) the relationship between vocabulary mastery and speaking skills. The research employed a quantitative approach with a correlational design. The sample consisted of 26 students selected using a simple random sampling technique. The instruments used were a vocabulary mastery test and a speaking skills test, while the data were analyzed using the Pearson Product Moment correlation test. The results showed that the average score for vocabulary mastery was 71.53 (categorized as good), while the average score for speaking skills was 68.65 (categorized as good). The correlation analysis produced a positive correlation coefficient of 0.44 with a tcount of 2.45, which is greater than ttable = 1.71 at a significance level of 0.05, indicating that Ha is accepted and Ho is rejected. The implication of this study is that higher vocabulary mastery significantly improves students' speaking skills. Therefore, teachers are encouraged to focus more on vocabulary instruction as a foundation for enhancing students’ speaking abilities in elementary school.